2017
DOI: 10.1002/cnm.2884
|View full text |Cite
|
Sign up to set email alerts
|

Face shield design against blast‐induced head injuries

Abstract: Blast-induced traumatic brain injury has been on the rise in recent years because of the increasing use of improvised explosive devices in conflict zones. Our study investigates the response of a helmeted human head subjected to a blast of 1 atm peak overpressure, for cases with and without a standard polycarbonate (PC) face shield and for face shields comprising of composite PC and aerogel materials and with lateral edge extension. The novel introduction of aerogel into the laminate face shield is explored an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…Goggles act similar to a face shield or a visor. Several studies 31,33,36,39,43 have shown the excellent ability of face shields in mitigating the ICP. For example, Tse et al 43 studied the protective performance of single-layered and multi-layered face shields for frontal blast exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Goggles act similar to a face shield or a visor. Several studies 31,33,36,39,43 have shown the excellent ability of face shields in mitigating the ICP. For example, Tse et al 43 studied the protective performance of single-layered and multi-layered face shields for frontal blast exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Goggles act similar to a face shield or a visor. Several studies 31 , 33 , 36 , 39 , 43 have shown the excellent ability of face shields in mitigating the ICP. For example, Tse et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These categories vary depending on the duration of the impulse of force during which an injury is sustained, and the distance from the epicenter of an event. As pointed out [2,4,[6][7][8][9], traumas arising from blast impact are experienced within 3 to 100 microseconds of an event and, with a ballistic impact, within about 200 microseconds. In this case, high temperature is also an additional element of trauma.…”
Section: Analysis Of Risks and Their Minimizationmentioning
confidence: 99%
“…Tan et al [15] have developed a virtual model of finite elements of a human head and a helmet in order to help in the design of the next generations of helmets for ballistic and explosion protection. They carried out simulations of the head (with and without the helmet) under explosion using a Eurelian-Lagrangian approach and using the CoBi-FEM code to simulate the problem.…”
Section: Introductionmentioning
confidence: 99%